Legal And Constitutional Evaluation Of The Nigerian Sovereign Wealth Fund - Ekokoi , Solomon E. (Journal of Sustainable Development Law and Policy, 2025)
The central aim of this paper is to examine the constitutionality of Nigeria’s sovereign wealth fund (SWF) which was established in August 2012, pursuant to the Nigeria Sovereign Investment Authority (Establishment etc) Act 2011 (the NSIA Act). The paper reviews and discusses how questions on the constitutionality of a sovereign wealth fund have been dealt with in other jurisdictions with similar legal and governmental structures. It reviews practices in the United States and Canada, where the establishment of SWFs conform to their federal constitutional designs; and in Australia and Russia, where the law and practice of SWF are similar to the extant regime in Nigeria. This paper argues that questions on the constitutional basis of the SWF alone should not affect the establishment of a national SWF in Nigeria and therefore recommends a constitutional amendment to clear the grey areas. It discusses the importance of the law and development approach in resolving the identifiable setbacks in the Nigerian NSIA Act bearing in mind the potentials of the SWF in the socio-economic development of the Nigeria.